Liquid composition set and method for producing electrochemical device

The use of a liquid composition set with specific viscosity and solubility properties addresses the solubility and dispersibility challenges in electrode materials, enhancing the design freedom and performance of electrode composite material layers in electrochemical devices.

JP7613035B2Active Publication Date: 2025-01-15RICOH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020161032
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-09-25
Publication Date
2025-01-15
Estimated Expiration
2040-09-25

AI Technical Summary

Technical Problem

Existing methods for forming electrode composite material layers in electrochemical devices face challenges in achieving optimal solubility and dispersibility of electrode materials in liquids with varying boiling points, limiting the design freedom and efficiency of the liquid composition.

Method used

A liquid composition set is used, comprising a first and second liquid composition with viscosities of 200 mPa·s or less at 25°C, where the second electrode material is more easily dissolved or dispersed in the second liquid, allowing for improved discharge characteristics and electrochemical device performance.

Benefits of technology

The liquid composition set provides a high degree of freedom in design, enabling the formation of electrode composite material layers with enhanced electrochemical characteristics and ejection stability, resulting in improved capacity and peel strength of the electrode composite material layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613035000003
    Figure 0007613035000003
  • Figure 0007613035000004
    Figure 0007613035000004
  • Figure 0007613035000005
    Figure 0007613035000005
Patent Text Reader

Abstract

To provide a liquid composition set that has a high degree of freedom in design and can be used for formation of a positive electrode mixed material layer or a negative electrode mixed material layer that constitutes an electrochemical element.SOLUTION: A liquid composition set is used for formation of a positive electrode mixed material layer or a negative electrode mixed material layer. The liquid composition set has a first liquid composition in which a first electrode material is dissolved or dispersed in a first liquid, and a second liquid composition in which a second electrode material different from the first electrode material is dissolved or dispersed in a second liquid different from the first liquid. The second electrode material is more easily dissolved or dispersed in the second liquid than in the first liquid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid composition set and a method for producing an electrochemical device. [Background technology]

[0002] Electrochemical elements such as lithium ion secondary batteries, electric double layer capacitors, lithium ion capacitors, and redox capacitors are being installed in portable devices, hybrid cars, electric cars, etc., and the demand for them is expanding. In addition, there is an increasing need for thin batteries to be installed in various wearable devices and medical patches, and the requirements for electrochemical elements are becoming more diverse.

[0003] Conventionally, as a manufacturing method for an electrode constituting an electrochemical element, a method has been known in which an electrode mixture layer is formed on an electrode substrate by applying an electrode material and a liquid composition for an electrode mixture layer, which contains a liquid, using a die coater, a comma coater, a reverse roll coater, or the like.

[0004] For example, the electrode mixture layer can be formed by screen printing the electrode mixture layer liquid composition on the electrode substrate.

[0005] However, in order to perform screen printing in a shape that meets the needs, it is necessary to prepare a screen for each need.

[0006] In view of this, a method has been investigated in which a liquid composition for an electrode mixture layer is discharged onto an electrode substrate using a liquid discharge device to form the electrode mixture layer (see, for example, Patent Documents 1 and 2). Summary of the Invention [Problem to be solved by the invention]

[0007] For example, from the viewpoint of the drying efficiency of the electrode mixture layer liquid composition, it is considered to use a liquid having a low boiling point as the liquid contained in the electrode mixture layer liquid composition.

[0008] However, electrode materials (eg, active materials, conductive assistants, binders, electrolytes, etc.) that provide good characteristics for electrochemical devices do not always have good solubility or dispersibility in the liquid with a low boiling point.

[0009] From the viewpoint of the ejection characteristics of the electrode mixture layer liquid composition, it is also possible to use a liquid having a high boiling point as the liquid contained in the electrode mixture layer liquid composition.

[0010] Therefore, when designing a liquid composition for an electrode mixture layer that provides good characteristics of an electrochemical element and good discharge characteristics, it is necessary to consider the electrochemical characteristics of the liquid and the electrochemical characteristics of the electrode material, as well as a number of other conditions such as the solubility and dispersibility of the electrode material in the liquid, etc. Therefore, it is desirable to improve the degree of freedom in designing the liquid composition for an electrode mixture layer.

[0011] An object of the present invention is to provide a liquid composition set which has a high degree of freedom in design and can be used to form a positive electrode mixture layer or a negative electrode mixture layer that constitutes an electrochemical device. [Means for solving the problem]

[0012] One aspect of the present invention is Using a liquid ejection device Positive electrode mixture layer or negative electrode mixture layer To form A liquid composition set comprising a first liquid composition in which a first electrode material is dissolved or dispersed in a first liquid, and a second liquid composition in which a second electrode material different from the first electrode material is dissolved or dispersed in a second liquid different from the first liquid, the first liquid composition and the second liquid composition each have a viscosity of 200 mPa s or less at 25°C; The second electrode material is more easily dissolved or dispersed in the second liquid than in the first liquid. Effect of the Invention

[0013] According to the present invention, it is possible to provide a liquid composition set which has a high degree of freedom in design and can be used to form a positive electrode mixture layer or a negative electrode mixture layer that constitutes an electrochemical device. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a negative electrode according to the present embodiment. [Diagram 2] 3A to 3C are schematic diagrams illustrating an example of a method for producing a negative electrode according to the present embodiment. [Diagram 3] 5A to 5C are schematic diagrams illustrating another example of the method for producing a negative electrode according to the present embodiment. [Figure 4] 5A to 5C are diagrams illustrating another example of the method for producing the negative electrode according to the present embodiment. [Diagram 5] 5A to 5C are diagrams illustrating another example of the method for producing the negative electrode according to the present embodiment. [Figure 6] FIG. 6 is a schematic diagram showing a modified example of the liquid ejection device of FIGS. [Figure 7] FIG. 2 is a cross-sectional view showing an example of a positive electrode of the present embodiment. [Figure 8] FIG. 2 is a cross-sectional view showing an example of an electrode element of the present embodiment. [Figure 9] FIG. 1 is a cross-sectional view showing an example of an electrochemical element according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the same components are denoted by the same reference numerals, and the description thereof will be omitted in some cases.

[0016] [Liquid composition set] The liquid composition set of the present embodiment is used to form a positive electrode mixture layer or a negative electrode mixture layer.

[0017] The liquid composition set of the present embodiment has a first liquid composition in which a first electrode material is dissolved or dispersed in a first liquid, and a second liquid composition in which a second electrode material different from the first electrode material is dissolved or dispersed in a second liquid different from the first liquid.

[0018] In this specification and claims, the term "liquid" refers to a liquid that functions as a medium for dissolving or dispersing the electrode material, and does not include a liquid that functions as a precursor of a binder (for example, a monomer).

[0019] Here, the first electrode material may contain at least one of an active material, a conductive additive, a binder, and an electrolyte, and preferably contains a conductive additive, which improves the characteristics of the electrochemical device.

[0020] The second electrode material may include at least one of an active material, a conductive assistant, a binder, and an electrolyte.

[0021] In the liquid composition set of the present embodiment, the second electrode material is more easily dissolved or dispersed in the second liquid than in the first liquid.

[0022] As a result, the liquid composition set of this embodiment provides a liquid composition set with high design freedom and excellent electrochemical element characteristics and ejection characteristics.

[0023] The liquid composition set of the present embodiment may include at least one of the first liquid composition and the second liquid composition.

[0024] Here, "at least one of the first liquid composition and the second liquid composition" refers to only the first liquid composition, only the second liquid composition, or both the first liquid composition and the second liquid composition.

[0025] Furthermore, having at least one of the first liquid composition and the second liquid composition refers to having one type each of the first liquid composition and the second liquid composition, having two or more types of the first liquid composition and one type of the second liquid composition, having one type of the first liquid composition and two or more types of the second liquid composition, or having two or more types of both the first liquid composition and the second liquid composition.

[0026] In general, the conditions under which any of the electrode active material, conductive assistant, binder, and electrolyte constituting the electrode mixture layer dissolves or disperses well in a liquid may differ depending on each of them. Also, even if any of the electrode active material, conductive assistant, binder, and electrolyte constituting the electrode mixture layer dissolves or disperses well in the same liquid, when these are mixed, they may not dissolve or disperse well.

[0027] If multiple types of electrode materials, including electrode active materials, conductive assistants, binders, and electrolytes, which are expected to have good characteristics for electrochemical elements, are dissolved or dispersed well in different liquids, it may be difficult to eject a liquid composition containing multiple types of these electrode materials.

[0028] Thus, by including at least one of the first liquid composition and the second liquid composition, the degree of freedom in designing the liquid composition is improved.

[0029] When at least one of the first electrode material and the second electrode material contains an active material, the content of the active material in the liquid composition is preferably 20% by mass or more, more preferably 25% by mass or more. When the content of the active material in the liquid composition is 20% by mass or more, the capacity of the electrochemical element is improved, and when it is 25% by mass or more, the capacity of the electrochemical element is further improved.

[0030] The content of the active material in the liquid composition is preferably 60% by mass or less. When the content of the active material in the liquid composition is 60% by mass or less, the ejection properties of the liquid composition are improved.

[0031] The first liquid composition and the second liquid composition preferably have a viscosity that allows them to be ejected from a liquid ejection head.

[0032] The viscosity of the liquid composition at 25° C. is preferably 200 mPa·s or less. When the viscosity of the liquid composition at 25° C. is 200 mPa·s or less, the ejection stability of the liquid composition is improved.

[0033] In this specification and claims, the electrode material being dissolved in a liquid means that the viscosity of the liquid composition at 25° C. is 200 mPa·s or less.

[0034] Furthermore, the second electrode material being more soluble in the second liquid than the first liquid means that when the second liquid in the second liquid composition is replaced with the first liquid, the viscosity at 25°C increases, or the second electrode material becomes insoluble in the first liquid.

[0035] It is preferable that the maximum particle diameter of the first electrode material and the second electrode material is smaller than the nozzle diameter of the liquid ejection head.

[0036] Here, the maximum particle size refers to the particle size at which the volumetric particle size distribution is 100%. The maximum particle size can be measured by a particle size distribution meter that uses a laser diffraction method.

[0037] The mode diameter of the first electrode material and the second electrode material is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 3 μm or less. When the mode diameter of the first electrode material and the second electrode material is 20 μm or less, the ejection stability and sedimentation resistance of the first liquid composition and the second liquid composition are improved, when it is 10 μm or less, the ejection stability and sedimentation resistance of the first liquid composition and the second liquid composition are further improved, and when it is 3 μm or less, the ejection stability and sedimentation resistance of the first liquid composition and the second liquid composition are further improved.

[0038] Here, the mode diameter refers to the particle size that is the most frequent value in the particle size distribution. The mode diameter can be measured by a particle size distribution meter that uses a laser diffraction method.

[0039] In this specification and claims, the electrode material being dispersed in a liquid means that the mode diameter of the liquid composition is 3 μm or less.

[0040] Furthermore, the second electrode material being more easily dispersible in the second liquid than in the first liquid means that when the second liquid in the second liquid composition is replaced with the first liquid, the mode diameter increases, or the second electrode material becomes less dispersible in the first liquid.

[0041] The 10% diameter (d10) of the first electrode material and the second electrode material is preferably 0.10 μm or more, and more preferably 0.15 μm or more. When the median diameter (d10) of the first electrode material and the second electrode material is 0.10 μm or more, the storage stability of the liquid composition is improved, and when it is 0.15 μm or more, the storage stability of the liquid composition is further improved.

[0042] The 10% diameter of the electrode material can be measured by a particle size distribution analyzer that utilizes a laser diffraction method.

[0043] <Active material> As the active material, a positive electrode active material or a negative electrode active material can be used.

[0044] The positive electrode active material or the negative electrode active material may be used alone or in combination of two or more kinds.

[0045] The positive electrode active material is not particularly limited as long as it is capable of absorbing or releasing alkali metal ions, and an alkali metal-containing transition metal compound can be used.

[0046] Here, the term "occlusion" refers to insertion of alkali metal ions into the negative electrode active material, and the term "release" refers to desorption of alkali metal ions from the negative electrode active material.

[0047] Examples of the alkali metal-containing transition metal compound include lithium-containing transition metal compounds such as composite oxides containing lithium and one or more elements selected from the group consisting of cobalt, manganese, nickel, chromium, iron, and vanadium.

[0048] Examples of the lithium-containing transition metal compound include lithium cobalt oxide, lithium nickel oxide, and lithium manganese oxide.

[0049] As for alkali metal-containing transition metal compounds, XO 4 Polyanion-based compounds having a tetrahedron (X is P, S, As, Mo, W, Si, etc.) can also be used. Among these, lithium-containing transition metal phosphate compounds such as lithium iron phosphate and lithium vanadium phosphate are preferred in terms of cycle characteristics, and lithium vanadium phosphate is particularly preferred in terms of lithium diffusion coefficient and output characteristics. In terms of electronic conductivity, it is preferable that the polyanion-based compound is surface-coated with a conductive assistant such as a carbon material to form a composite.

[0050] The negative electrode active material is not particularly limited as long as it is capable of absorbing or releasing alkali metal ions, and a carbon material containing graphite having a graphite-type crystal structure can be used.

[0051] Examples of carbon materials include natural graphite, artificial graphite, non-graphitizable carbon (hard carbon), and easily graphitizable carbon (soft carbon).

[0052] Examples of negative electrode active materials other than carbon materials include lithium titanate and titanium oxide.

[0053] From the viewpoint of the energy density of the nonaqueous electricity storage element, it is preferable to use a high-capacity material such as silicon, tin, a silicon alloy, a tin alloy, silicon oxide, silicon nitride, or tin oxide as the negative electrode active material.

[0054] <Electrolyte> As the electrolyte, a material for forming a solid electrolyte layer can be used. The material for forming the solid electrolyte layer is not particularly limited as long as it is a solid substance having electronic insulation and ion conductivity, but a sulfide-based solid electrolyte or an oxide-based solid electrolyte is preferable from the viewpoint of having high ion conductivity.

[0055] As a sulfide-based solid electrolyte, for example, Li 10 GeP 2 S 12 or Li with argyrodite-type crystal structure 6 P.S. 5 X (wherein X is F, Cl, Br, or I).

[0056] As an example of an oxide-based solid electrolyte, there is LLZ (Li 7 La 3 Zr 2 O 12 ) or LATP (Li 1+x Al x Ti20 x (PO 4 ) 3 )(0.1≦x≦0.4), LLT(Li 0.33 La 0.55 TiO 3 ), amorphous LIPON(Li 2.9 PO 3.3 N 0.4 ) etc.

[0057] These solid electrolytes may be used alone or in combination of two or more.

[0058] The electrolyte material to be dissolved or dispersed in the liquid to form these solid electrolyte layers is, for example, Li, which is a precursor of the solid electrolyte. 2 S, P 2 S 5 Li, LiCl, and other solid electrolyte materials 2 SP 2 S 5 Glasses containing Li 7 P 3 S 11 Glass ceramics, etc.

[0059] Moreover, a material for forming a gel electrolyte layer can also be used as the electrolyte.

[0060] The gel electrolyte is not particularly limited as long as it exhibits ionic conductivity. For example, polymers constituting the network structure of the gel electrolyte include polyethylene oxide, polypropylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinyl chloride, copolymers of vinylidene fluoride and propylene hexafluoride, and polyethylene carbonate.

[0061] In addition, examples of the solvent molecules held in the gel electrolyte include ionic liquids, such as methyl-1-propylpyrrolidinium bis(fluorosulfonylimide), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonylimide), 1-methyl-1-propylpiperidinium bis(fluorosulfonylimide), 1-ethyl-3-methylimidazolium bis(fluorosulfonylimide), 1-methyl-3-propylimidazolium bis(fluorosulfonylimide), and N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonylimide).

[0062] Alternatively, a mixture of a liquid such as tetraglyme, propylene carbonate, fluoroethylene carbonate, ethylene carbonate, or diethyl carbonate and a lithium salt may be used.

[0063] The lithium salt is not particularly limited and can be appropriately selected depending on the purpose. For example, lithium hexafluorophosphate (LiPF 6 ), lithium borofluoride (LiBF 4 ), lithium arsenic hexafluoride (LiAsF 6 ), lithium trifluoromethasulfonate (LiCF 3 SO 3 ), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF 3 SO 2 ) 2 ), lithium bis(pentafluoroethylsulfonyl)imide (LiN(C 2 F 5 SO 2 ) 2 ) etc.

[0064] The gel electrolyte may be used alone or in combination of two or more kinds.

[0065] To form these gel electrolyte layers, the electrolyte material to be dissolved or dispersed in the liquid may be a solution in which the above-mentioned polymer compound and an ionic liquid or lithium salt are dissolved. Alternatively, the electrolyte material to be dissolved or dispersed in the liquid may be a material that serves as a precursor of the gel electrolyte (for example, a combination of polyethylene oxide or polypropylene oxide having acrylate groups at both ends and a solution in which an ionic liquid or a lithium salt is dissolved).

[0066] <Liquid> The liquid is not particularly limited as long as it is capable of dispersing the positive electrode material or the negative electrode material, and examples of the liquid include water, ethylene glycol, propylene glycol, trimethylene glycol, N-methyl-2-pyrrolidone, 2-pyrrolidone, cyclohexanone, ethyl lactate, butyl acetate, mesitylene, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, 2-n-butoxymethanol, 2-dimethylethanol, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, normal hexane, heptane, octane, nonane, decane, diethyl ether, dibutyl ether, di-tert-butyl ether, toluene, xylene, anisole, and mesitylene.

[0067] The liquids may be used alone or in combination of two or more kinds.

[0068] <Conductive additive> As the conductive assistant, for example, conductive carbon black formed by a furnace method, an acetylene method, a gasification method, or the like, as well as carbon materials such as carbon nanofibers, carbon nanotubes, graphene, and graphite particles can be used.

[0069] As the conductive assistant other than the carbon material, for example, metal particles such as aluminum, metal fibers, etc. can be used.

[0070] <Binder> There are no particular limitations on the binder as long as it is capable of binding together negative electrode materials, between positive electrode materials, between a negative electrode material and a negative electrode substrate, and between a positive electrode material and a positive electrode substrate. However, from the viewpoint of preventing nozzle clogging of the liquid ejection head, it is preferable to use a material that does not increase the viscosity of the liquid composition.

[0071] As a material that does not increase the viscosity of the liquid composition, a polymer compound that can be dissolved or dispersed in the liquid can be used.

[0072] When a polymer compound that can be dissolved in a liquid is used, the liquid composition in which the polymer compound is dissolved in the liquid has a viscosity that allows it to be ejected from a liquid ejection head.

[0073] Examples of polymer compounds include polyamide compounds, polyimide compounds, polyamideimide, ethylene-propylene-butadiene rubber (EPBR), styrene-butadiene rubber (SBR), nitrile butadiene rubber (HNBR), isoprene rubber, polyisobutene, polyethylene glycol (PEO), polymethyl methacrylic acid (PMMA), and polyethylene vinyl acetate (PEVA).

[0074] As the polymer compound that can be dissolved in a liquid, polymer particles may be used.

[0075] The maximum particle diameter of the polymer particles needs to be smaller than the nozzle diameter of the liquid ejection head.

[0076] The mode diameter of the polymer particles is preferably 0.01 to 1 μm.

[0077] Examples of materials constituting the polymer particles include thermoplastic resins such as polyvinylidene fluoride, acrylic resin, styrene-butadiene rubber, polyethylene, polypropylene, polyurethane, nylon, polytetrafluoroethylene, polyphenylene sulfide, polyethylene terephthalate, and polybutylene terephthalate.

[0078] Furthermore, the electrode material of the present embodiment may contain other electrode materials, such as a binder precursor and a dispersant, as long as the effects of the present invention are not impaired.

[0079] <Binder precursor> Examples of the binder precursor include polymerizable compounds such as monomers.

[0080] In the case of using a polymerizable compound, for example, a liquid composition in which the polymerizable compound is dissolved in a liquid is applied, and then the liquid composition is heated or irradiated with non-ionizing radiation, ionizing radiation, infrared radiation, or the like, whereby polymerization occurs and the binder is generated.

[0081] The polymerizable compound is not particularly limited as long as it has a polymerizable group, but a compound capable of being polymerized at 25°C is preferred.

[0082] By using a polymerizable compound, a plurality of pores can be formed inside the electrode mixture layer. In this case, it is preferable that the pores inside the electrode mixture layer are connected to each other and spread three-dimensionally. By connecting the pores, the electrolyte can sufficiently permeate the electrode mixture layer, improving the ionic conductivity of the electrochemical element.

[0083] The polymerizable compound may be monofunctional or polyfunctional.

[0084] The polyfunctional polymerizable compound means a compound having two or more polymerizable groups.

[0085] The polyfunctional polymerizable compound is not particularly limited as long as it can be polymerized by heating or irradiation with nonionizing radiation, ionizing radiation, or infrared radiation, and examples thereof include acrylate resins, methacrylate resins, urethane acrylate resins, vinyl ester resins, unsaturated polyesters, epoxy resins, oxetane resins, vinyl ethers, resins utilizing ene-thiol reactions, etc. Among these, from the viewpoint of productivity, acrylate resins, methacrylate resins, urethane acrylate resins, and vinyl ester resins are preferred.

[0086] A multifunctional acrylate resin can be used as a Michael acceptor, and can undergo a polyaddition reaction with a Michael donor.

[0087] Examples of polyfunctional acrylate resins include difunctional acrylates such as low molecular weight compounds such as dipropylene glycol diacrylate and neopentyl glycol diacrylate, and high molecular weight compounds such as polyethylene glycol diacrylate, urethane acrylate and epoxy acrylate; trifunctional acrylates such as trimethylolpropane triacrylate and pentaerythritol triacrylate; and tetrafunctional or higher acrylates such as pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate.

[0088] Examples of the Michael donor include polyfunctional amines and polyfunctional thiols.

[0089] Examples of polyfunctional amines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,2-phenylenediamine, 1,3-phenylenediamine, and 1,4-phenylenediamine.

[0090] Examples of polyfunctional thiols include 1,2-ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 2,3-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 1,3,5-benzenetrithiol, and 4,4-biphenyldithiol.

[0091] As the catalyst for the polyaddition reaction, any catalyst commonly used in the Michael addition reaction can be appropriately selected and used, and examples thereof include amine catalysts such as diazabicycloundecene (DBU) and N-methyldicyclohexylamine, base catalysts such as sodium methoxide, sodium ethoxide, potassium t-butoxide, sodium hydroxide, and tetramethylammonium hydroxide, metallic sodium, and butyllithium.

[0092] Examples of polymerizable compounds capable of addition polymerization (radical polymerization) include esters obtained by epoxylating the double bonds of terpenes having unsaturated bonds, such as myrcene, carene, ocimene, pinene, limonene, camphene, terpinolene, tricyclene, terpinene, fenchene, phellandrene, sylvestrene, sabinene, dipentene, bornene, isopulegol, and carvone, and adding acrylic acid or methacrylic acid thereto; citronellol, pinocampheol, geraniol, and fenchyl. Alcohol, nerol, borneol, linalool, menthol, terpineol, thuyl alcohol, citronellal, ionone, iron, cinerol, citral, pinol, cyclocitral, carbomenthone, ascaridole, safranal, piperitol, menthenomonool, dihydrocarvone, carveol, sclareol, manol, hinokiol, ferruginol, totarol, sugiol, farnesol, patchouli alcohol, nerolidol, carotol, cajillool Esters of alcohols derived from terpenes such as nol, lantheol, eudesmol, and phytol with acrylic or methacrylic acid; citronellic acid, hinoki acid, and santalic acid; menthone, carbotanetone, ferrandrale, pimelitenone, perillaldehyde, thujone, calone, dagetone, camphor, bisabolene, santalene, zingiberene, caryophyllene, curcumene, cedrene, cadinene, longifolene, sesquibenihen, cedrol, guayol, kessoglycol, and cypero Examples of the acrylate or methacrylate include those having a skeleton of a side chain such as ketomanoyl oxide, eremophilone, zerumbone, campholene, podocarpurene, myrene, phyllocladene, totarene, ketomanoyl oxide, manoyl oxide, abietic acid, pimaric acid, neoabietic acid, levopimaric acid, iso-d-pimaric acid, agathene dicarboxylic acid, rubenic acid, carotenoid, perarylaldehyde, piperitone, ascaridole, pimene, fencken, sesquiterpenes, diterpenes, or triterpenes.

[0093] As the polymerization initiator, for example, a photopolymerization initiator or a thermal polymerization initiator can be used.

[0094] As the photopolymerization initiator, a photoradical generator can be used.

[0095] Examples of the photoradical generator include α-hydroxyacetophenone, α-aminoacetophenone, 4-aroyl-1,3-dioxolane, benzil ketal, 2,2-diethoxyacetophenone, p-dimethylaminoacetophenone, p-dimethylaminopropiophenone, benzophenone, 2-chlorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bis(diethylamino)benzophenone, Michler's ketone, benzil, benzoin, benzil dimethyl ketal, tetramethylthiuram monosulfide, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, azobisisobutyronitrile, benzoin peroxide, di-tert-butyl peroxide, (1-hydroxy cyclohexyl)phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, methyl benzoyl formate, benzoin isopropyl ether, benzoin methyl ether, benzoin ethyl ether, benzoin isobutyl ether, benzoin n-butyl ether, benzoin n-propyl ether and other benzoin alkyl ethers, (1-hydroxycyclohexyl)phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1, (1-hydroxycyclohexyl)phenyl ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(η 5-2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one (Darocur 1173), bis(2,6-dimethoxybenzoyl) -2,4,4-trimethylpentylphosphine oxide, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, monoacylphosphine oxide, diacylphosphine oxide, titanocene, fluorescene, anthraquinone, thioxanthone, xanthone, lophine dimer, trihalomethyl compounds, dihalomethyl compounds, active ester compounds, and organic boron compounds.

[0096] A photocrosslinking type radical generator such as a bisazide compound such as 2,2'-azobis(2,4-dimethylvaleronitrile) may be used in combination with the photoradical generator.

[0097] An example of the thermal polymerization initiator is azobisisobutyronitrile (AIBN).

[0098] A photoacid generator may be used as the polymerization initiator. In this case, when the applied liquid composition is irradiated with light, the photoacid generator generates an acid, which polymerizes the polymerizable compound.

[0099] Examples of the polymerizable compound that polymerizes in the presence of an acid include monomers having a vinyl group that can undergo cationic polymerization, such as compounds having a cyclic ether group such as an epoxy group, an oxetane group, or an oxolane group, acrylic compounds or vinyl compounds having the above-mentioned cyclic ether group on a side chain, carbonate compounds, low molecular weight melamine compounds, vinyl ethers, vinyl carbazoles, styrene derivatives, α-methylstyrene derivatives, and vinyl alcohol esters such as ester compounds of vinyl alcohol with acrylic acid, methacrylic acid, or the like.

[0100] Examples of the photoacid generator include onium salts, diazonium salts, quinone diazides, organic halides, aromatic sulfonates, disulfone compounds, sulfonyl compounds, sulfonates, sulfonium salts, sulfamides, iodonium salts, sulfonyldiazomethane compounds, etc. Among these, onium salts are preferred.

[0101] Examples of the onium salt include diazonium salts, phosphonium salts, and sulfonium salts having a fluoroborate ion, a hexafluoroantimonate ion, a hexafluoroarsenate ion, a trifluoromethanesulfonate ion, or a p-toluenesulfonate ion as a counter ion.

[0102] As the photoacid generator other than the above, a halogenated triazine can be used.

[0103] The photoacid generators may be used alone or in combination of two or more. When a photoacid generator is used, a sensitizing dye may be used in combination.

[0104] Examples of sensitizing dyes include acridine, benzoflavin, perylene, anthracene, and laser dyes.

[0105] <Dispersant> The liquid composition may further comprise a dispersant.

[0106] The dispersant is not particularly limited as long as it is capable of improving the dispersibility of the electrode material in the liquid. Examples of the dispersant include polymer dispersants such as polycarboxylic acid-based, naphthalenesulfonic acid-formalin condensation-based, polyethylene glycol, polycarboxylic acid partial alkyl ester-based, polyether-based, and polyalkylene polyamine-based dispersants; low molecular weight dispersants such as alkylsulfonic acid-based, quaternary ammonium-based, higher alcohol alkylene oxide-based, polyhydric alcohol ester-based, and alkyl polyamine-based dispersants; and inorganic dispersants such as polyphosphate-based dispersants.

[0107] [Method of manufacturing electrochemical element] The method for producing an electrochemical device of this embodiment includes a step of applying the liquid composition set of this embodiment onto an electrode substrate to form an electrode mixture layer.

[0108] Here, examples of methods for applying the liquid composition set onto an electrode substrate include a method in which the liquid compositions constituting the liquid composition set are applied sequentially onto an electrode substrate, and a method in which the liquid compositions constituting the liquid composition set are applied approximately simultaneously onto an electrode substrate.

[0109] The method for applying the liquid composition is not particularly limited, and examples thereof include spin coating, casting, microgravure coating, gravure coating, bar coating, roll coating, wire bar coating, dip coating, slit coating, capillary coating, spray coating, nozzle coating, gravure printing, screen printing, flexographic printing, offset printing, reverse printing, liquid ejection, etc. Among these, the liquid ejection is particularly preferred in terms of electrode productivity.

[0110] In the case where the liquid composition contains a polymerizable compound, the liquid composition is applied onto an electrode substrate, and then heated or irradiated with non-ionizing radiation, ionizing radiation, infrared radiation, or the like, whereby the polymerizable compound is polymerized to produce a binder.

[0111] There are no particular limitations on the material constituting the electrode substrate (current collector) so long as it is conductive and stable to the applied potential.

[0112] <Negative electrode> FIG. 1 shows an example of the negative electrode of this embodiment.

[0113] Negative electrode 10 has a negative electrode mixture layer 12 formed on one surface of a negative electrode substrate 11 .

[0114] Negative electrode mixture layer 12 may be formed on both sides of negative electrode substrate 11 .

[0115] The shape of the negative electrode 10 is not particularly limited, and examples thereof include a flat plate shape.

[0116] Examples of materials constituting the negative electrode substrate 11 include stainless steel, nickel, aluminum, and copper.

[0117] <Method of manufacturing the negative electrode> FIG. 2 shows an example of a method for producing the negative electrode of this embodiment.

[0118] The method for producing the negative electrode 10 includes the steps of sequentially discharging a first liquid composition 12A and a second liquid composition 12B onto the negative electrode substrate 11 using liquid dischargers 300A and 300B.

[0119] Here, the liquid composition contains a negative electrode material, and the negative electrode material contains a negative electrode active material, a conductive assistant, and a binder or a binder precursor.

[0120] The liquid composition 12A is stored in a tank 307A, and is supplied from the tank 307A to the liquid ejection head 306A via a tube 308A. Similarly, the liquid composition 12B is stored in a tank 307B, and is supplied from the tank 307B to the liquid ejection head 306B via a tube 308B.

[0121] The number of liquid ejection devices is not limited to two, but may be three or more.

[0122] Furthermore, the liquid ejection device 300A (or 300B) may be provided with a mechanism for capping the nozzle to prevent the liquid composition 12A (or 12B) from drying out when the liquid composition 12A (or 12B) is not being ejected from the liquid ejection head 306A (or 306B).

[0123] When manufacturing the negative electrode 10, the negative electrode substrate 11 is placed on a heatable stage 400, and then droplets of the first liquid composition 12A and the second liquid composition 12B are ejected from the liquid ejection heads 306A and 306B in this order onto the negative electrode substrate 11. At this time, the stage 400 may move, or the liquid ejection heads 306A and 306B may move.

[0124] Furthermore, when the liquid composition 12A discharged onto the negative electrode substrate 11 is heated, it may be heated by the stage 400 or may be heated by a heating mechanism other than the stage 400.

[0125] The heating mechanism is not particularly limited as long as it does not come into direct contact with first liquid composition 12A and second liquid composition 12B, and examples thereof include a resistance heater, an infrared heater, and a fan heater.

[0126] A plurality of heating mechanisms may be provided.

[0127] In addition, an ultraviolet curing device for polymerizing the polymerizable compound may be provided.

[0128] The heating temperature is not particularly limited as long as it is a temperature at which the polymerizable compound is polymerized, and is preferably in the range of 70 to 150° C. from the viewpoint of energy usage.

[0129] Furthermore, when the liquid composition 12A discharged onto the negative electrode substrate 11 is heated, it may be irradiated with ultraviolet light.

[0130] In the method for producing a negative electrode according to this embodiment, negative electrode mixture layer 12 is formed on negative electrode substrate 11, and negative electrode 10 is obtained.

[0131] FIG. 3 shows another example of the method for producing the negative electrode of this embodiment.

[0132] The method for producing the negative electrode 10 includes the step of sequentially discharging a first liquid composition 12A and a second liquid composition 12B onto the negative electrode substrate 11 using a liquid discharge apparatus 300C.

[0133] Liquid composition 12A is stored in tank 307A and is supplied from tank 307A to liquid ejection head 306C via tube 308A. Similarly, liquid composition 12B is stored in tank 307B and is supplied from tank 307B to liquid ejection head 306C via tube 308B.

[0134] When manufacturing the negative electrode 10, the negative electrode substrate 11 is placed on a heatable stage 400, and then droplets of the first liquid composition 12A and the second liquid composition 12B are ejected, in sequence, onto the negative electrode substrate 11 from the liquid ejection head 306C.

[0135] FIG. 4 shows another example of the method for producing the negative electrode of this embodiment.

[0136] The method for producing the negative electrode 10 includes the steps of sequentially discharging a first liquid composition 12A and a second liquid composition 12B onto the negative electrode substrate 11 using liquid dischargers 300A and 300B.

[0137] First, an elongated negative electrode substrate 11 is prepared. Then, the negative electrode substrate 11 is wound around a cylindrical core, and set on a feed roller 304 and a take-up roller 305 so that the side on which the negative electrode composite layer 12 is formed is the upper side in the figure. Here, the feed roller 304 and the take-up roller 305 rotate counterclockwise, and the negative electrode substrate 11 is transported in a direction from right to left in the figure. Then, droplets of the first liquid composition 12A and droplets of the second liquid composition 12B are sequentially discharged onto the negative electrode substrate 11 being transported from liquid discharge heads 306A and 306B installed above the negative electrode substrate 11 between the feed roller 304 and the take-up roller 305 in the same manner as in FIG. 2. The droplets of the first liquid composition 12A and droplets of the second liquid composition 12B are discharged so as to cover at least a part of the negative electrode substrate 11.

[0138] A plurality of liquid ejection heads 306A and 306B may be installed in a direction substantially parallel to or substantially perpendicular to the direction in which the negative electrode substrate 11 is transported.

[0139] Also, similarly to FIG. 3, a liquid ejection device 300C may be installed in place of the liquid ejection devices 300A and 300B (see FIG. 5).

[0140] Next, negative electrode substrate 11 onto which droplets of first liquid composition 12A and second liquid composition 12B have been discharged is transported to heating mechanism 309 by delivery roller 304 and take-up roller 305. As a result, first liquid composition 12A and second liquid composition 12B on negative electrode substrate 11 are dried to form negative electrode mixture layer 12, and negative electrode 10 is obtained. Thereafter, negative electrode 10 is cut to a desired size by punching or the like.

[0141] There are no particular limitations on the heating mechanism 309, so long as it does not come into direct contact with the first liquid composition 12A and the second liquid composition 12B, and examples thereof include a resistance heater, an infrared heater, and a fan heater.

[0142] The heating mechanism 309 may be provided either above or below the negative electrode substrate 11, or a plurality of heating mechanisms may be provided.

[0143] The heating temperature is not particularly limited as long as it is a temperature at which the polymerizable compound is polymerized, and is preferably in the range of 70 to 150° C. from the viewpoint of energy usage.

[0144] Furthermore, when the liquid composition 12A discharged onto the negative electrode substrate 11 is heated, it may be irradiated with ultraviolet light.

[0145] FIG. 6 shows modified examples of liquid ejection devices 300A and 300B.

[0146] The liquid ejection device 300A' can circulate the first liquid composition 12A through the liquid ejection head 306A, the tank 307A, and the tube 308A by controlling the pump 310A and the valves 311A ​​and 312A. Similarly, the liquid ejection device 300B' can circulate the second liquid composition 12B through the liquid ejection head 306B, the tank 307B, and the tube 308B by controlling the pump 310B and the valves 311B and 312B.

[0147] Furthermore, the liquid ejection device 300A' is provided with an external tank 313A, and when the first liquid composition 12A in the tank 307A decreases, it is also possible to supply the first liquid composition 12A from the external tank 313A to the tank 307A by controlling the pump 310A and the valves 311A, 312A, and 314A. Similarly, the liquid ejection device 300B' is provided with an external tank 313B, and when the second liquid composition 12B in the tank 307B decreases, it is also possible to supply the second liquid composition 12B from the external tank 313B to the tank 307B by controlling the pump 310B and the valves 311B, 312B, and 314B.

[0148] By using the liquid ejection device, first liquid composition 12A and second liquid composition 12B can be ejected to a targeted location of negative electrode substrate 11 (a region of negative electrode substrate 11 where negative electrode mixture layer 12 is to be formed). In addition, by using the liquid ejection device, the contacting surfaces above and below negative electrode substrate 11 and negative electrode mixture layer 12 can be bonded to each other. Furthermore, by using the liquid ejection device, the thickness of negative electrode mixture layer 12 can be made uniform.

[0149] <Positive electrode> FIG. 7 shows an example of the positive electrode of this embodiment.

[0150] The positive electrode 20 has a positive electrode mixture layer 22 formed on one surface of a positive electrode substrate 21 .

[0151] Positive electrode mixture layer 22 may be formed on both sides of positive electrode substrate 21 .

[0152] The shape of the positive electrode 20 is not particularly limited, and may be, for example, a flat plate shape.

[0153] Examples of materials constituting the positive electrode substrate 21 include stainless steel, aluminum, titanium, and tantalum.

[0154] <Manufacturing method of positive electrode> The method for producing positive electrode 20 is the same as that for producing negative electrode 10, except that positive electrode mixture layer 22 is formed on positive electrode substrate 21.

[0155] Here, the liquid composition contains a positive electrode material, and the positive electrode material contains a positive electrode active material, a conductive assistant, and a binder or a binder precursor.

[0156] <Electrode element> FIG. 8 shows an example of an electrode element used in the electrochemical device of this embodiment.

[0157] In the electrode element 40, a negative electrode 15 and a positive electrode 25 are laminated with a separator 30 interposed therebetween. Here, the positive electrode 25 is laminated on both sides of the negative electrode 15. In addition, a lead wire 41 is connected to the negative electrode substrate 11, and a lead wire 42 is connected to the positive electrode substrate 21.

[0158] Negative electrode 15 is similar to negative electrode 10 except that negative electrode mixture layer 12 is formed on both sides of negative electrode substrate 11 .

[0159] Positive electrode 25 is similar to positive electrode 20 except that positive electrode mixture layers 22 are formed on both sides of positive electrode substrate 21 .

[0160] The number of layers of the negative electrodes 15 and the positive electrodes 25 of the electrode element 40 is not particularly limited.

[0161] Furthermore, the number of negative electrodes 15 and the number of positive electrodes 25 in the electrode element 40 may be the same or different.

[0162] <separator> A separator 30 is provided between the negative electrode 15 and the positive electrode 25 as necessary to prevent a short circuit between the negative electrode 15 and the positive electrode 25 .

[0163] Examples of the separator 30 include paper such as kraft paper, vinylon-mixed paper, and synthetic pulp-mixed paper, cellophane, polyethylene graft membrane, polyolefin nonwoven fabric such as polypropylene melt-blown nonwoven fabric, polyamide nonwoven fabric, glass fiber nonwoven fabric, and micropore membrane.

[0164] There is no particular limitation on the size of the separator 30 as long as it can be used in an electrochemical element.

[0165] The separator 30 may have a single layer structure or a laminate structure.

[0166] When a solid electrolyte is used, the separator 30 can be omitted.

[0167] <Electrochemical element> FIG. 9 shows an example of the electrochemical device of this embodiment.

[0168] 8, an electrolyte layer 51 is formed by injecting an electrolyte aqueous solution or a non-aqueous electrolyte into an electrode element 40 shown in FIG.

[0169] The electrochemical device 1 may include other members as necessary.

[0170] The electrochemical element 1 is not particularly limited, and examples thereof include an aqueous electricity storage element and a non-aqueous electricity storage element.

[0171] The shape of the electrochemical element 1 is not particularly limited, and examples thereof include a laminate type, a cylinder type in which a sheet electrode and a separator are spirally wound, a cylinder type with an inside-out structure in which a pellet electrode and a separator are combined, and a coin type in which a pellet electrode and a separator are stacked.

[0172] <Aqueous electrolyte solution> Examples of electrolyte salts constituting the aqueous electrolyte solution include sodium hydroxide, potassium hydroxide, sodium chloride, potassium chloride, ammonium chloride, zinc chloride, zinc acetate, zinc bromide, zinc iodide, zinc tartrate, and zinc perchlorate.

[0173] <Non-aqueous electrolyte> As the non-aqueous electrolyte, a solid electrolyte or a non-aqueous electrolyte solution can be used.

[0174] Here, the non-aqueous electrolyte is an electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent.

[0175] <Non-aqueous solvent> The non-aqueous solvent is not particularly limited, and it is preferable to use, for example, an aprotic organic solvent.

[0176] As the aprotic organic solvent, a carbonate-based organic solvent such as a chain carbonate, a cyclic carbonate, etc. Among these, a chain carbonate is preferred because of its high dissolving power for the electrolyte salt.

[0177] In addition, the aprotic organic solvent preferably has a low viscosity.

[0178] Examples of the chain carbonate include dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC).

[0179] The content of the chain carbonate in the non-aqueous solvent is preferably 50% by mass or more. When the content of the chain carbonate in the non-aqueous solvent is 50% by mass or more, even if the non-aqueous solvent other than the chain carbonate is a cyclic substance with a high dielectric constant (e.g., a cyclic carbonate, a cyclic ester), the content of the cyclic substance is small. Therefore, even if a non-aqueous electrolyte solution with a high concentration of 2M or more is prepared, the viscosity of the non-aqueous electrolyte solution is low, and the non-aqueous electrolyte solution is absorbed into the electrode and ions are diffused well.

[0180] Examples of cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), and vinylene carbonate (VC).

[0181] Examples of non-aqueous solvents other than carbonate-based organic solvents include ester-based organic solvents such as cyclic esters and chain esters, and ether-based organic solvents such as cyclic ethers and chain ethers. etc. can be used.

[0182] Examples of cyclic esters include γ-butyrolactone (γBL), 2-methyl-γ-butyrolactone, acetyl-γ-butyrolactone, and γ-valerolactone.

[0183] Examples of chain esters include alkyl propionates, dialkyl malonates, alkyl acetates (eg, methyl acetate (MA), ethyl acetate), and alkyl formates (eg, methyl formate (MF), ethyl formate).

[0184] Examples of cyclic ethers include tetrahydrofuran, alkyltetrahydrofuran, alkoxytetrahydrofuran, dialkoxytetrahydrofuran, 1,3-dioxolane, alkyl-1,3-dioxolane, and 1,4-dioxolane.

[0185] Examples of the chain ether include 1,2-dimethoxyethane (DME), diethyl ether, ethylene glycol dialkyl ether, diethylene glycol dialkyl ether, triethylene glycol dialkyl ether, and tetraethylene glycol dialkyl ether.

[0186] <Electrolyte salt> There are no particular limitations on the electrolyte salt, so long as it has high ionic conductivity and is soluble in a non-aqueous solvent.

[0187] The electrolyte salt preferably contains a halogen atom.

[0188] Examples of cations constituting the electrolyte salt include lithium ions.

[0189] Examples of anions constituting the electrolyte salt include BF 4 - , P.F. 6 - , AsF 6 - , C.F. 3 SO 3 - , (CF 3 SO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - etc.

[0190] The lithium salt is not particularly limited and can be appropriately selected depending on the purpose. For example, lithium hexafluorophosphate (LiPF 6 ), lithium borofluoride (LiBF 4 ), lithium arsenic hexafluoride (LiAsF 6 ), lithium trifluoromethasulfonate (LiCF 3 SO 3 ), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF 3 SO 2 )2 ), lithium bis(pentafluoroethylsulfonyl)imide (LiN(C 2 F 5 SO 2 ) 2 Among these, LiPF is the most popular from the viewpoint of ionic conductivity. 6 is preferred, and from the viewpoint of stability, LiBF 4 is preferred.

[0191] The electrolyte salts may be used alone or in combination of two or more kinds.

[0192] The concentration of the electrolyte salt in the nonaqueous electrolyte can be appropriately selected depending on the purpose, but when the nonaqueous storage element is of a swing type, it is preferably 1 mol / L to 2 mol / L, and when the nonaqueous storage element is of a reserve type, it is preferably 2 mol / L to 4 mol / L.

[0193] <Applications of electrochemical elements> Applications of electrochemical elements are not particularly limited, and examples thereof include notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, mobile fax machines, mobile copiers, mobile printers, headphone stereos, video movie machines, liquid crystal televisions, handheld cleaners, portable CDs, mini discs, transceivers, electronic organizers, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, lighting equipment, toys, game equipment, clocks, strobes, cameras, and the like. EXAMPLES

[0194] Examples of the present invention will be described below, but the present invention is not limited to these examples. Note that in the examples of the present invention, applications in which the electrode material is a positive electrode active material or a negative electrode active material will be described, but the same applies to applications in which the electrode material is an electrode material other than a positive electrode active material or a negative electrode active material.

[0195] [Particle size distribution of liquid composition] The liquid composition was dispersed in water or an organic solvent, and then the particle size distribution of the liquid composition was measured at 25° C. using a laser diffraction particle size distribution analyzer Mastersizer 3000 (manufactured by Malvern Instruments).

[0196] [Viscosity of liquid composition] A No. CPA-40Z rotor was attached to a Brookfield viscometer (cone-plate viscometer) and the viscosity of the liquid composition at 100 rpm was measured at 25°C.

[0197] [Peel strength of electrode mixture layer] The peel strength of the electrode composite layer was measured using an adhesive / film peeling analyzer VPA-3 (manufactured by Kyowa Interface Science Co., Ltd.) (peel strength test method). Specifically, the electrode was cut into a test piece with a width of 1.8 cm and a length of 10 cm, and cellophane tape was attached to the surface of the electrode composite layer side of the test piece. After that, the cellophane tape was peeled off 100 mm from one end of the test piece at a peeling speed of 30 mm / min and a peeling angle of 90°, and the stress at that time was measured. This stress measurement was carried out 10 times, and the weighted average of the stress was calculated to obtain the peel strength of the electrode composite layer.

[0198] [Capacity of positive electrodes A to F and A'] The positive electrode was punched out into a circle with a diameter of 16 mm, and then the positive electrode, a 100 μm thick glass separator (manufactured by ADVANTEC), non-aqueous electrolyte 1, and a 200 μm thick lithium counter electrode (manufactured by Honjo Metals) were placed in a coin can to obtain a non-aqueous storage element.

[0199] 0.1mA / cm2 at room temperature (25°C) for non-aqueous storage elements 2 After charging to a charge cut-off voltage of 4.2 V, the battery was charged at a constant current of 0.1 mA / cm 2 The initial charge / discharge was carried out by discharging at a constant current of 0.1 mA / cm 2 After constant current charging to 4.2 V at 0.1 mA / cm 2 The charge-discharge cycle was performed twice, in which the battery was discharged at a constant current of 100 V to 3.0 V, and the capacity per unit area of ​​the positive electrode was measured.

[0200] The capacity per unit area of ​​the electrode was measured using a charge / discharge measuring device TOSCAT3001 (manufactured by Toyo Systems Co., Ltd.).

[0201] [Capacity of negative electrode A] The negative electrode was punched out into a circle with a diameter of 16 mm, and then the negative electrode, a 100 μm thick glass separator (manufactured by ADVANTEC Corporation), nonaqueous electrolyte 1, and a 200 μm thick lithium (manufactured by Honjo Metals Co., Ltd.) as a counter electrode were placed in a coin can to prepare a nonaqueous storage element.

[0202] 0.1mA / cm2 at room temperature (25°C) for non-aqueous storage elements 2 After charging to a charge cut-off voltage of 1.0 V, the battery was charged at a constant current of 0.1 mA / cm 2 The initial charge / discharge was carried out by discharging at a constant current of 0.1 mA / cm 2 After charging to 1.0 V at a constant current of 0.1 mA / cm 2 A constant current discharge cycle was performed twice, in which the battery was discharged at a constant current of 1.0 V at 0.5 V to 2.0 V, and the capacity per unit area of ​​the negative electrode was measured.

[0203] [Capacity of negative electrode B] The negative electrode was punched out into a circle with a diameter of 16 mm, and then the negative electrode, a 100 μm thick glass separator (manufactured by ADVANTEC Corporation), nonaqueous electrolyte 1, and a 200 μm thick lithium (manufactured by Honjo Metals Co., Ltd.) as a counter electrode were placed in a coin can to prepare a nonaqueous storage element.

[0204] 0.4mA / cm2 at room temperature (25°C) for non-aqueous storage elements 2 After charging to a charge cut-off voltage of 0.2 V, the battery was charged at a constant current of 0.4 mA / cm 2 The initial charge / discharge was carried out by discharging at a constant current of 0.1 mA / cm 2 After charging to 0.2 V at a constant current of 0.4 mA / cm 2 A constant current discharge cycle was performed twice, in which the battery was discharged at a constant current of 1.0 V at 0.5 V to 2.0 V, and the capacity per unit area of ​​the negative electrode was measured.

[0205] [Cathode active material 1] Vanadium pentoxide, lithium hydroxide, phosphoric acid, sucrose, and water were mixed to generate a precipitate, which was then pulverized to obtain a precursor of vanadium phosphate particles. Next, the vanadium phosphate precursor was fired at 900°C in a nitrogen atmosphere to obtain lithium vanadium phosphate (LVP) with a carbon content of 3 mass%. The LVP had a mode diameter of 10 μm. The LVP was further crushed using a jet mill to obtain positive electrode active material 1. The positive electrode active material 1 had a mode diameter of 0.7 μm and a capacity per unit area of ​​0.26 mAh / cm. 2 It was.

[0206] [Cathode active material 2] A nickel-based positive electrode active material (NCA) (manufactured by JFE Mineral Co., Ltd.) was crushed using a jet mill to obtain a positive electrode active material 2. The positive electrode active material 2 had a mode diameter of 1.5 μm and a capacity per unit area of ​​0.35 mAh / cm. 2 It was.

[0207] [Cathode active material 3] Lithium cobalt oxide (LCO) (manufactured by Toshima Manufacturing Co., Ltd.) was crushed using a bead mill to obtain a positive electrode active material 3. The positive electrode active material 3 had a mode diameter of 1.3 μm and a capacity per unit area of ​​0.23 mAh / cm. 2 It was.

[0208] [Cathode active material 4] Lithium manganese oxide (LMO) (manufactured by Toshima Manufacturing Co., Ltd.) was crushed using a bead mill to obtain a positive electrode active material 4. The positive electrode active material 4 had a mode diameter of 1.3 μm and a capacity per unit area of ​​0.31 mAh / cm. 2 It was.

[0209] [Cathode active material 5] Lithium iron phosphate (LFP) (manufactured by TATUNG FINE CHEMICALS) was crushed using a bead mill to obtain a positive electrode active material 5. The positive electrode active material 5 had a mode diameter of 1.0 μm and a capacity per unit area of ​​0.33 mAh / cm. 2 It was.

[0210] [Cathode active material 6] Nickel-based positive electrode active material (NCA) (manufactured by JFE Mineral Co., Ltd.) was crushed using a bead mill. Thus, positive electrode active material 6 was obtained. Positive electrode active material 6 had a mode diameter of 9.6 μm and a capacity per unit area of ​​0.35 mAh / cm 2 It was.

[0211] [Negative electrode active material 1] Lithium titanate (LTO) (manufactured by Ishihara Sangyo Kaisha) was crushed using a bead mill to obtain negative electrode active material 1. Negative electrode active material 1 had a mode diameter of 2.0 μm and a capacity per unit area of ​​0.31 mAh / cm 2 It was.

[0212] [Negative electrode active material 2] Silicon monoxide (SiO) (manufactured by Osaka Titanium Co., Ltd.) was crushed using a bead mill to obtain a negative electrode active material 2. The negative electrode active material 2 had a mode diameter of 1.0 μm and a capacity per unit area of ​​2.0 mAh / cm 2 It was.

[0213] Table 1 shows the evaluation results of the mode diameter (μm) of the active material and the capacity per unit area.

[0214] [Table 1]

[0215] [Non-aqueous electrolyte 1] LiPF was dissolved in a 1.0 mol / L mixture of propylene carbonate (PC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) in a mass ratio of 1:1:1. 6 The above was dissolved to prepare non-aqueous electrolyte solution 1 (20 mL).

[0216] Example 1 Positive electrode active material 1 (30 mass%) as the positive electrode active material, carbon black (3 mass%) as the conductive assistant, and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare a first liquid composition, Liquid Composition A. Liquid Composition A had a viscosity of 10.3 mPa s and a mode diameter of 1.58 μm.

[0217] Polyamideimide (3 mass%) as a binder and N-methylpyrrolidone (NMP) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (97 mass%) were mixed to prepare a second liquid composition, Liquid Composition B. Liquid Composition B contained polyamideimide dissolved in N-methylpyrrolidone (NMP) and had a viscosity of 9.6 mPa s.

[0218] When polyamideimide (3% by mass) and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (97%) were mixed to prepare a liquid composition, the liquid composition became cloudy and precipitates were generated. In other words, polyamideimide, which is the second electrode material, is more easily dissolved in N-methylpyrrolidone, which is the second liquid, than ethyl lactate, which is the first liquid.

[0219] Using a liquid ejection device EV2500, liquid compositions A and B were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode A. At this time, the aluminum foil was fixed onto a hot plate and heated to 130° C. Liquid compositions A and B had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 2.0 mg / cm. 2 The positive electrode mixture layer was formed, and Liquid Compositions A and B had good discharge efficiency.

[0220] Positive electrode A has a peel strength of 1.05 N and a capacity per unit area of ​​0.26 mAh / cm 2 It was.

[0221] Example 2 A positive electrode A was obtained in the same manner as in Example 1, except that the liquid compositions A and B were discharged onto an aluminum foil as shown in FIG. 3 using a liquid discharge device EV2500. The liquid compositions A and B had good discharge stability and no discharge failure occurred. As a result, the amount of active material per unit area was 1.9 mg / cm. 2 The positive electrode mixture layer was formed, and Liquid Compositions A and B had good discharge efficiency.

[0222] Positive electrode A has a peel strength of 1.09 N and a capacity per unit area of ​​0.25 mAh / cm 2 It was.

[0223] Example 3 A positive electrode A was obtained in the same manner as in Example 1, except that the liquid compositions A and B were discharged onto an aluminum foil as shown in FIG. 4 using a liquid discharge device EV2500. The liquid compositions A and B had good discharge stability and no discharge failure occurred. As a result, the amount of active material per unit area was 1.9 mg / cm. 2 The positive electrode mixture layer was formed, and Liquid Compositions A and B had good discharge efficiency.

[0224] Positive electrode A has a peel strength of 1.11 N and a capacity per unit area of ​​0.25 mAh / cm 2 It was.

[0225] Example 4 A positive electrode A was obtained in the same manner as in Example 1, except that the liquid compositions A and B were discharged onto an aluminum foil as shown in FIG. 5 using a liquid discharge device EV2500. The liquid compositions A and B had good discharge stability and no discharge failure occurred. As a result, the amount of active material per unit area was 2.1 mg / cm. 2 The positive electrode mixture layer was formed, and Liquid Compositions A and B had good discharge efficiency.

[0226] Positive electrode A has a peel strength of 1.08 N and a capacity per unit area of ​​0.27 mAh / cm 2 It was.

[0227] Example 5 Positive electrode active material 2 (30 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare a first liquid composition, Liquid Composition C. Liquid Composition C had a viscosity of 10.3 mPa s and a mode diameter of 2.52 μm.

[0228] Polyamideimide (3 mass%) and N,N-dimethylacetamide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (97 mass%) were mixed to prepare a second liquid composition, Liquid Composition D. In Liquid Composition D, polyamideimide was dissolved in N,N-dimethylacetamide, and the viscosity was 9.6 mPa s.

[0229] When polyamideimide (3% by mass) and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (97%) were mixed to prepare a liquid composition, the liquid composition became cloudy and precipitates were generated. In other words, polyamideimide, which is the second electrode material, is more easily dissolved in N,N-dimethylacetamide, which is the second liquid, than ethyl lactate, which is the first liquid.

[0230] Using a liquid ejection device EV2500, liquid compositions C and D were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode B. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid compositions C and D had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 2.2 mg / cm. 2 The positive electrode mixture layer could be formed, and Liquid Compositions C and D had good discharge efficiency.

[0231] Positive electrode B has a peel strength of 1.14 N and a capacity per unit area of ​​0.36 mAh / cm 2 It was.

[0232] Example 6 Positive electrode active material 3 (30 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare a first liquid composition, Liquid Composition E. Liquid Composition E had a viscosity of 10.7 mPa s and a mode diameter of 1.22 μm.

[0233] Using a liquid ejection device EV2500, liquid compositions E and D were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode C. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid compositions E and D had good ejection stability and did not cause ejection defects. As a result, the amount of active material per unit area was 2.0 mg / cm. 2 The positive electrode mixture layer could be formed, and Liquid Compositions E and D had good discharge efficiency.

[0234] Positive electrode C has a peel strength of 1.05 N and a capacity per unit area of ​​0.23 mAh / cm 2 It was.

[0235] Example 7 Positive electrode active material 4 (30 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare a first liquid composition, Liquid Composition F. Liquid Composition F had a viscosity of 11.1 mPa s and a mode diameter of 1.48 μm.

[0236] Using a liquid ejection device EV2500, liquid compositions F and D were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode D. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid compositions F and D had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 2.0 mg / cm. 2 The positive electrode mixture layer could be formed, and Liquid Compositions F and D had good discharge efficiency.

[0237] Positive electrode D has a peel strength of 1.08 N and a capacity per unit area of ​​0.25 mAh / cm 2 It was.

[0238] Example 8 Positive electrode active material 5 (30 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare a first liquid composition, Liquid Composition G. Liquid Composition G had a viscosity of 10.9 mPa s and a mode diameter of 2.11 μm.

[0239] Using a liquid ejection device EV2500, liquid compositions G and D were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode E. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid compositions G and D had good ejection stability and did not cause ejection defects. As a result, the amount of active material per unit area was 2.1 mg / cm. 2 The positive electrode mixture layer could be formed, and Liquid Compositions G and D had good discharge efficiency.

[0240] Positive electrode E has a peel strength of 1.09 N and a capacity per unit area of ​​0.30 mAh / cm 2 It was.

[0241] Example 9 Negative electrode active material 1 (30 mass%), carbon black (1 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (69 mass%) were mixed to prepare a first liquid composition, Liquid Composition H. Liquid Composition H had a viscosity of 10.1 mPa s and a mode diameter of 1.05 μm.

[0242] Using a liquid ejection device EV2500, liquid compositions H and B were ejected onto an aluminum foil as shown in FIG. 2 to obtain a negative electrode A. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid compositions H and B had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 2.1 mg / cm. 2 The negative electrode mixture layer could be formed, and Liquid Compositions H and B had good discharge efficiency.

[0243] Negative electrode A has a peel strength of 1.05 N and a capacity per unit area of ​​0.32 mAh / cm 2 It was.

[0244] Example 10 Negative electrode active material 2 (30 mass%), carbon black (1 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (69 mass%) were mixed to prepare a first liquid composition, Liquid Composition I. Liquid Composition I had a viscosity of 13.1 mPa s and a mode diameter of 2.15 μm.

[0245] Using a liquid ejection device EV2500, liquid compositions I and B were ejected onto a copper foil as shown in FIG. 2 to obtain a negative electrode B. At this time, the copper foil was fixed on a hot plate and heated to 120° C. Liquid compositions I and B had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 1.9 mg / cm. 2 The negative electrode mixture layer could be formed, and Liquid Compositions I and B had good discharge efficiency.

[0246] Negative electrode B has a peel strength of 1.08 N and a capacity per unit area of ​​2.0 mAh / cm 2 It was.

[0247] Example 11 Polyamideimide (6 mass%) and N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (94 mass%) were mixed to prepare liquid composition B' as a second liquid composition. In liquid composition B', polyamideimide was dissolved in N-methylpyrrolidone and had a viscosity of 9.6 mPa s.

[0248] When polyamideimide (6 mass%) and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (94%) were mixed to prepare a liquid composition, the liquid composition became cloudy and precipitates were generated. In other words, polyamideimide, which is the second electrode material, is more easily dissolved in N-methylpyrrolidone, which is the second liquid, than ethyl lactate, which is the first liquid.

[0249] Using a liquid ejection device EV2500, liquid compositions A and B' were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode A. At this time, the aluminum foil was fixed onto a hot plate and heated to 130°C. Liquid compositions A and B' had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 2.2 mg / cm 2 The positive electrode mixture layer was formed, and the liquid compositions A and B' had good discharge efficiency.

[0250] Positive electrode A has a peel strength of 2.17 N and a capacity per unit area of ​​0.26 mAh / cm 2 It was.

[0251] Example 12 Positive electrode active material 6 (40 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (57 mass%) were mixed to prepare a first liquid composition, Liquid Composition J. Liquid Composition J had a viscosity of 11.9 mPa s and a mode diameter of 9.11 μm.

[0252] Using a liquid ejection device EV2500, the liquid compositions J and B were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode F. At this time, the aluminum foil was fixed on a hot plate and heated to 120° C. The liquid compositions J and B had good ejection stability and did not cause ejection defects. As a result, a positive electrode composite layer with an active material amount per unit area of ​​2.1 mg / cm2 could be formed, and the liquid compositions J and B had good ejection efficiency.

[0253] Positive electrode F had a peel strength of the positive electrode mixture of 1.13 N and a capacity per unit area of ​​0.34 mAh / cm2.

[0254] (Example 13) Positive electrode active material 6 (50 mass%), carbon black (3 mass%), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (47 mass%) were mixed to prepare a first liquid composition, liquid composition K. Liquid composition K had a viscosity of 13.9 mPa s and a mode diameter of 9.41 μm.

[0255] Using a liquid ejection device EV2500, the liquid compositions K and B were ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode F. At this time, the aluminum foil was fixed onto a hot plate and heated to 120°C. The liquid compositions K and B had good ejection stability and did not cause ejection defects. As a result, a positive electrode composite layer with an active material amount per unit area of ​​2.2 mg / cm2 could be formed, and the liquid compositions K and B had good ejection efficiency.

[0256] Positive electrode F has a peel strength of 1.09 N and a capacity per unit area of ​​0.36 mAh / cm2.

[0257] Comparative Example 1 Positive electrode active material 1 (30% by mass), carbon black (3% by mass), polyamideimide (3% by mass), and ethyl lactate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (64% by mass) were mixed to prepare liquid composition L. However, liquid composition L gelled and could not be discharged.

[0258] Comparative Example 2 Negative electrode active material 2 (30% by mass), carbon black (10% by mass), polyamideimide (3% by mass), and N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (57% by mass) were mixed to prepare liquid composition M, but the viscosity of liquid composition M increased. Liquid composition M had a mode diameter of 11.5 μm and could not be discharged.

[0259] Comparative Example 3 Positive electrode active material 1 (30 mass%), carbon black (3 mass%), polyamideimide (3 mass%), and N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (64 mass%) were mixed to prepare Liquid Composition N. Liquid Composition N had a viscosity of 13.5 mPa s and a mode diameter of 1.71 μm.

[0260] Using a liquid ejection device EV2500, liquid composition N was ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode A. At this time, the aluminum foil was fixed onto a hot plate and heated to 120° C. Liquid composition N had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 1.9 mg / cm. 2 The positive electrode mixture layer was formed, and Liquid Composition N had good discharge efficiency.

[0261] Positive electrode A has a peel strength of 1.01 N and a capacity per unit area of ​​0.24 mAh / cm 2 It was.

[0262] Comparative Example 4 Positive electrode active material 1 (30 mass%), carbon black (3 mass%), and N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (67 mass%) were mixed to prepare Liquid Composition N'. Liquid Composition N' had a viscosity of 10.2 mPa s and a mode diameter of 1.71 μm.

[0263] Using a liquid ejection device EV2500, liquid composition N' was ejected onto an aluminum foil as shown in FIG. 2 to obtain a positive electrode A'. At this time, the aluminum foil was fixed onto a hot plate and heated to 120°C. Liquid composition N' had good ejection stability and no ejection failure occurred. As a result, the amount of active material per unit area was 1.9 mg / cm 2 The positive electrode mixture layer was formed, and the liquid composition N' had good discharge efficiency.

[0264] For positive electrode A', the peel strength of the positive electrode mixture was 0.002 N, so the capacity per unit area could not be measured.

[0265] Table 2 shows the evaluation results of the amount of active material per unit area, the peel strength of the electrode mixture layer, and the capacity of the electrode.

[0266] The abbreviations for the liquids are as follows: NMP: N-methylpyrrolidone DMA: N,N-Dimethylacetamide

[0267] [Table 2]

[0268] From Table 2, it can be seen that the electrodes of Examples 1 to 13 have good active material amount per unit area, peel strength of the electrode mixture layer, and electrode capacity, and have high design freedom. For example, the electrode of Example 11 has a high peel strength of the electrode mixture layer due to the increased amount of binder added.

[0269] In contrast, in Comparative Example 1, a single liquid composition L containing ethyl lactate, which was used in the liquid composition A of Examples 1 to 4 and 11, was prepared when the positive electrode A was produced, and thus gelation occurred.

[0270] In Comparative Example 2, when negative electrode B was produced, a single liquid composition M containing NMP used in liquid composition B of Example 10 was produced, and therefore the viscosity increased.

[0271] In Comparative Example 3, the amount of active material per unit area of ​​the electrode, the peel strength of the electrode mixture layer, and the capacity of the electrode are good, but the degree of freedom in designing the liquid composition N is low.

[0272] In Comparative Example 4, the liquid composition N' does not contain a binder, so the peel strength of the electrode mixture layer is low. [Explanation of symbols]

[0273] 1. Electrochemical element 10, 15 negative electrode 11 Negative electrode substrate 12 Negative electrode composite layer 12A First Liquid Composition 12B Second Liquid Composition 20, 25 positive electrode 21 Positive electrode substrate 22 Positive electrode mixture layer 30 Separator 40 Electrode element 41, 42 Lead wire 51 Electrolyte layer 52 Exterior packaging

Prior art documents

Patent documents

[0274]

Patent Document 1

Patent Document 2

Claims

1. A liquid composition set for forming a positive electrode composite layer or a negative electrode composite layer using a liquid ejection device, comprising: a first liquid composition in which a first electrode material is dissolved or dispersed in a first liquid; a second liquid composition in which a second electrode material different from the first electrode material is dissolved or dispersed in a second liquid different from the first liquid; the first liquid composition and the second liquid composition each have a viscosity of 200 mPa·s or less at 25° C.; The second electrode material is more easily dissolved or dispersed in the second liquid than in the first liquid.

2. The liquid composition set according to claim 1 , comprising at least one of the first liquid composition and the second liquid composition.

3. The liquid composition set according to claim 1 , wherein the first liquid composition and the second liquid composition each have a viscosity that enables the first liquid composition to be ejected from a liquid ejection head of the liquid ejection device.

4. The liquid composition set according to claim 1 , wherein the first electrode material includes a conductive assistant.

5. At least one of the first electrode material and the second electrode material contains an active material, The liquid composition set according to claim 1 , wherein the active material is a material capable of absorbing or releasing alkali metal ions.

6. At least one of the first electrode material and the second electrode material contains an active material, The liquid composition set according to claim 1 , wherein the liquid composition containing the active material has a content of the active material of 20 mass % or more.

7. The liquid composition set according to claim 1 , wherein the first electrode material and the second electrode material have a maximum particle size smaller than a nozzle diameter of a liquid ejection head of the liquid ejection device.

8. The liquid composition set according to claim 1 , wherein the first electrode material and the second electrode material have a mode diameter of 3 μm or less.

9. A liquid composition set described in any one of claims 1 to 8, wherein the first liquid composition contains ethyl lactate.

10. A liquid composition set described in any one of claims 1 to 9, wherein the second liquid composition contains N-methylpyrrolidone or N,N-dimethylacetamide.

11. A method for producing an electrochemical element, comprising the step of applying the liquid composition set according to claim 1 onto an electrode substrate to form an electrode mixture layer.

Citation Information

Patent Citations

  • Protection circuit for power output circuit

    JP1980071304A

  • Fluorouracil derivative and antitumor agent

    JP1984013780A

  • Nonaqueous secondary battery and its manufacturing method

    JP2003163006A

  • Non-aqueous electrolyte battery

    JP2005050755A

  • Manufacturing method of electrode catalyst layer

    JP2006172914A